A Bibliometric Analysis of 20 Years of Globalization Research: 1990-2009 - Liu, Xingjian; Hong, Song; Liu, Yaolin (Globalizations, 2012)
We present a bibliometric analysis of globalization research published during 1990-2009, based on three online library catalogues, the Science Citation Index, and the Social Science Citation Index databases. Our analysis summarizes major research patterns in globalization research and could serve as an alternative and potential guide for future research in this field. The volume of books and articles on globalization has exploded since the 1990s, and there is an even distribution of globalization literature across subject categories, reflecting the interdisciplinary nature of globalization research. International organizations appear as the most cited authors in globalization research. A keyword analysis suggests that cities and networks have a central position in studies of contemporary globalization and reveals several major strands in globalization studies. Presentamos un análisis bibliométrico de la investigación sobre la globalización publicado entre los años 1990 y 2009, basados en tres catálogos bibliográficos en línea, la base de datos del Índice de citas de la ciencia y del Índice de citas de la ciencia social. Nuestro análisis resume patrones importantes de indagación en la investigación de la globalización y podría servir como una guía alterna y potencial para futura investigación en este campo. El volumen de libros y artículos sobre globalización ha explotado desde los años de 1990 y existe una distribución uniforme sobre la literatura de la globalización entre las categorías de la materia, que reflejan la naturaleza interdisciplinaria de la investigación de la globalización. Un análisis de la palabra clave sugiere que las ciudades y las redes tienen una posición central en los estudios de la globalización contemporánea y que revela tendencias principales en los estudios de la globalización. 我们以图书馆目录、科学引文索引，以及社会科学引文索引三个在线的数据库为基础，提供了关于1990至2009年间发表的全球化研究的一个文献计量分析。我们的研究概括了全球化研究中的主要研究模式，可作为该领域未来研究的替代性和潜在性的指导。自1990年代以来，关于全球化的论著册子呈爆炸式涌现，各学科门类中全球化文献呈均匀分布，反映了全球化研究的学科间属性。国际组织在全球化研究中作为被最常援引的作者而出现。关键词的分析表明城市和网络在当代全球化研究中处于中心地位，这也反映了全球化研究的几个主要分支。 우리는 1990년부터 2009년까지 세 가지 온라인 도서관 카탈로그와 SCI 및 SSCI를 토대로 세계화에 관련된 출판물에 대한 서지측정 분석을 제시하고자 한다. 이 연구는 세계화 연구의 주요 유형들을 요약하고 미래 이 분야 연구에서 대안적이고 잠재적인 지침을 줄 수 있다. 1990년대 이래 세계화에 대한 책과 논문들이 폭발적으로 늘어 났고 학문 경계를 넘어서는 세계화 연구 결과들이 고르게 나타났으며, 이는 통합학문적인 세계화 연구 성격을 보여준다. 국제기구들이 세계화 연구에서 가장 많이 인용되는 저자들이다. 열쇠말 분석을 통하여 도시와 네트워크가 현대 세계화 연구에서 중심적인 위치를 차지하고 있으며 또한 이들이 세계화 연구 흐름을 보여준다는 것을 알 수 있다.